Immune cell profiles associated with measured exposure to phthalates in the Norwegian EuroMix biomonitoring study – A mass cytometry approach in toxicology. (January 2021) - Nygaard, Unni C.; Ulriksen, Emilie S.; Hjertholm, Hege; Sonnet, Friederike; Bølling, Anette K.; Andreassen, Monica; Husøy, Trine; Dirven, Hubert
Highlights: High-dimensional single cell analyses/immune cell profiling of human PBMC. Urinary phthalate levels (∑DEHP + DiNP) associated with specific immune cell clusters. Phthalates may stimulate/activate subsets of innate cells and suppress adaptive cells. A novel approach to study effects of environmental factors on the immune system. Abstract: Background: Phthalate exposure has been associated with immune-related diseases such as asthma and allergies, but there is limited knowledge on mechanisms, effect biomarkers and thus biological support of causality. Objectives: To investigate associations between exposure to the phthalates DEHP (di(2-ethylhexyl) phthalate) and DiNP (diisononyl phthalate) and functional immune cell profiles. Methods: Peripheral blood mononuclear cells (PBMCs) from 32 healthy adult Norwegian participants in the EuroMix biomonitoring study were selected based on high or low (n = 16) levels of urine metabolites of DEHP and DiNP. High-dimensional immune cell profiling including phenotyping and functional markers was performed by mass cytometry (CyTOF) using two broad antibody panels after PMA/ionomycin-stimulation. The CITRUS algorithm with unsupervised clustering was used to identify group differences in cell subsets and expression of functional markers, verified by manual gating. Results: The group of participants with high phthalate exposure had a higher proportion of some particular innate immune cells, including CD11c positive NK-cell and intermediate monocyte subpopulations. The percentage of IFNγ TNFα double positive NK cells and CD11b expression in other NK cell subsets were higher in the high exposure group. Among adaptive immune cells, however, the percentage of IL-6 and TNFα expressing naïve B cell subpopulations and the percentage of particular naïve cytotoxic T cell populations were lower in the high exposure group. Discussion: Cell subset percentages and expression of functional markers suggest that DEHP and DiNP phthalate exposure may stimulate subsets of innate immune cells and suppress adaptive immune cell subsets. By revealing significant immunological differences even in small groups, this study illustrates the promise of the broad and deep information obtained by high-dimensional single cell analyses of human samples to answer toxicological questions regarding health effects of environmental exposures.